Testing of chlorine dosage in drinking water using microstrip patch sensor - Anwer Sabah Mekki; Siba Monther Yousif; Mustafa Mohammed Jawad Abed (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2023)
A new method using microstrip patch sensor is designed, simulated, and measured to detect the dosage of added chlorine to the drinking water using the relation between permittivity and matching impedance. The simulation is done using computer simulation technology-microwave studio software. The proposed sensor is designed on a single FR-4 layer with a low profile, 0.499 GHz bandwidth, center frequency of 2.94 GHz, gain of 6.55 dBi, and a good front to back ratio of 17.84 dB. In this work, the antenna design is started from a conventional patch antenna equation. Then, an optimization process is performed to achieve good parameter values for obtaining the desired objective. The objective is to utilize the microwave frequency to measure the chlorine dosage in water. The measurement results proved that the matching impedance can be used to find out the dosage of chlorine in drinkable water. The proposed method overcomes the open-ended coaxial probe method in terms of experimental time and contactless testing and shows high matching with the latter actual data. Moreover, the proposed method overcomes the conventional methods in terms of continuity and large scale of testing, non-contacting with the samples of water, and no additive chemical materials, which make the water samples not drinkable.